2005
DOI: 10.1007/s00213-005-2239-x
|View full text |Cite
|
Sign up to set email alerts
|

Randomized clinical trial to compare the effects of methadone and buprenorphine on the immune system in drug abusers

Abstract: The effects of buprenorphine and methadone tested on the immune system were overlapping in our patients. The elevated cytokine levels observed may suggest that the two drugs stimulate immunologic hyperactivation of an immune system that was formerly inhibited by heroin. Furthermore, our data suggest that buprenorphine can be a valid alternative to methadone in maintenance treatment of chronic heroin abuse and referred a marked decline in depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 19 publications
(36 reference statements)
1
56
1
1
Order By: Relevance
“…The cause of high levels of ascorbic acid in melatonin-or vE + Se-treated groups may be related to either an activation of ascorbic acid synthesis or an inhibition of ascorbic acid degradation. Furthermore, studies on heroin addicts have revealed that the heroin exposure causes immunosuppression [37,38]. Decrease in vitamin C level may contribute to the derangement of immune functions in heroin-addicted person.…”
Section: Discussionmentioning
confidence: 97%
“…The cause of high levels of ascorbic acid in melatonin-or vE + Se-treated groups may be related to either an activation of ascorbic acid synthesis or an inhibition of ascorbic acid degradation. Furthermore, studies on heroin addicts have revealed that the heroin exposure causes immunosuppression [37,38]. Decrease in vitamin C level may contribute to the derangement of immune functions in heroin-addicted person.…”
Section: Discussionmentioning
confidence: 97%
“…However, many of the trials on which the Cochrane review was based (Fischer et al, 1999;Johnson et al, 2000;Lintzeris et al, 2004;Mattick et al, 2000;Neri et al, 2001;Petitjean et al, 2001;Strain, Stitzer, Liebson, & Bigelow, 1994) used relatively low doses of buprenorphine with slow inflexible induction, and this may have skewed the retention rates in favor of methadone. In addition, there is virtually no research identifying features that predict a better outcome with either drug or directly examining other outcomes, such as social functioning or psychological health, to guide the clinician in deciding whether indeed both drugs are equally appropriate.…”
Section: Introductionmentioning
confidence: 97%
“…Direct action of drugs on the immune cells, or indirect action via stimulation of the central and autonomous nervous system and the hypothalamus-pituitary-adrenal axis, are implicated in these complex alterations. Immunosuppression caused by drug abuse increases susceptibility to opportunistic infections, and drug addicts' lifestyles increase exposure to infectious pathogens [11]. Although we screened the immune profile of our patient because of her history of drug abuse, it did not show any meaningful deviation from normal.…”
Section: Discussionmentioning
confidence: 98%